Peran Layanan Bimbingan Kelompok dengan Teknik Problem Solving untuk Meningkatkan Pemahaman Kesehatan Mental Siswa - Rara Sari'ah Natasya Nurjanah; Eka Sari Setianingsih; Desi Maulia (Universitas Sebelas Maret, 2025)
Abstract: Understanding mental health is a very important aspect for students. The results of the analysis show that students' understanding of mental health is still lacking. This research aims to determine the role of group guidance services using problem solving techniques on the understanding of mental health represented by students. The method used in this research is quantitative research with a true experimental type with a pretest posttest control group design model, using a questionnaire with a Likert scale. The initial condition regarding understanding of students' mental health was found to be 10% in the very low category, 80% of students in the low category, and 20% in the high category for the experimental group. The control group received the low category with a presentation of 90% and the high category with a percentage of 10%. After being provided with group guidance services using problem solving techniques. Students' mental health understanding increased to 20% in the very high category and in the high category with a percentage of 80%. Meanwhile, the control class received the low category with a presentation of 90% and the high category with a percentage of 10%. The research results show that group guidance services using problem solving techniques can influence and improve students' understanding of mental health. It can be concluded that there is a significant influence on the understanding of mental health of students before and after group guidance services using problem solving techniques.